2021
DOI: 10.3390/molecules26020373
|View full text |Cite
|
Sign up to set email alerts
|

Ellagitannin–Lipid Interaction by HR-MAS NMR Spectroscopy

Abstract: Ellagitannins have antimicrobial activity, which might be related to their interactions with membrane lipids. We studied the interactions of 12 different ellagitannins and pentagalloylglucose with a lipid extract of Escherichia coli by high-resolution magic angle spinning NMR spectroscopy. The nuclear Overhauser effect was utilized to measure the cross relaxation rates between ellagitannin and lipid protons. The shifting of lipid signals in 1H NMR spectra of ellagitannin–lipid mixture due to ring current effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…The idea was that the higher the heat the addition of each HT produces is an indication of the degree to which the HT is able to interact with the lipid vesicles, or inversely if the HT molecules do not interact with lipid vesicles. Similarly, in our recent high-resolution magic angle spinning nuclear magnetic resonance (HR-MAS NMR) spectroscopic study using the same lipid extract and a subset of the same HTs used in this study, the importance of certain structural features was observed [ 25 ]. The initial premise was that the same features would prove dominant in this thermodynamic study as well.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…The idea was that the higher the heat the addition of each HT produces is an indication of the degree to which the HT is able to interact with the lipid vesicles, or inversely if the HT molecules do not interact with lipid vesicles. Similarly, in our recent high-resolution magic angle spinning nuclear magnetic resonance (HR-MAS NMR) spectroscopic study using the same lipid extract and a subset of the same HTs used in this study, the importance of certain structural features was observed [ 25 ]. The initial premise was that the same features would prove dominant in this thermodynamic study as well.…”
Section: Resultsmentioning
confidence: 63%
“…This correlated with our previous results. Vescalagin is highly hydrophilic and has not shown any interaction with the lipids studied by HR-MAS NMR measurements [ 25 , 28 ]. The 1 C 4 ellagitannins ( 12 – 15 ) also produced heats that were barely detectable, which was expected based on the results of our previous NMR study, where it was shown that geraniin ( 12 ) did not move spatially close to these phospholipid vesicles [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations